Applied Multipolarity: The Impact of the Ukrainian Crisis on India's Economy and Politics - E. Ya. Arapova; N. Yu. Silaev (Сравнительная политика)
The article aims to reflect the approaches of the Indian authorities and business to the Ukrainian crisis and cooperation with Russia in the context of anti-Russian sanctions after February 2022. The analysis is based on a dataset of Indian press, broadcasting statements by Indian officials and business representatives on cooperation with Russia, as well as an assessment of Indian companies’ behavior in the Russian market after the start of the Special Military Operation. The analysis showed that, while representatives of the Indian authorities are inclined to perceive Russia’s actions with restrained criticism, Indian business is striving to take advantage of the opportunities that the “sanctions war” has opened up for them in the Russian and other foreign markets.